Competition aspects of pricing access to networks: what are the issues? - Michie, J (Elsevier, 1998)
The introduction of competition between service providers in industries with some sort of network - such as telecommunications, but also gas and electricity - has created the regulatory problem of access pricing. Where a service provider requires access to a network owned by another firm, how much should that other firm be allowed to charge for access to its network? The problem arises where no agreement is forthcoming through normal market negotiations. The paper discusses the question of access pricing in telecoms, and the issues involved in actually deriving a price fixing mechanism for access to a network.